Between a man and a woman? : why conservatives oppose same-sex marriage - Viefhues-Bailey, Ludger H., 1965- (Gender, theory, and religion., 2010)
While conservative Christian groups refuse to recognize same-sex marriage, there is more to their debate than biblical literalism or nostalgia for simple gender roles. Investigating why conservative Christians are so energized by an issue that, according to their own statistics, affects only a small number of Americans, Ludger Viefhues-Bailey confronts a profound theological conundrum: conservatives of both sexes are asked at once to be assertive and submissive, masculine and feminine, both within the home, the church, society, and the state. Focusing primarily on texts produced.